2020
DOI: 10.3390/su12156193
|View full text |Cite
|
Sign up to set email alerts
|

Target-Oriented Promotion of the Intention for Sustainable Behavior with Social Norms

Abstract: To date, measures to promote sustainable behavior by influencing attitudes have often not had the expected success. Past research indicates that using social norms to promote sustainable behavior in people with low involvement in environmental protection offers a promising basis to address this problem. In this study, this insight was transferred to the context of two environmental measures at an early stage of development by investigating the effects of social norms on the intention for sustainable behavior i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The demographics section included gender, age, status, area of residence, education level, employment, total monthly household income, and the frequency of considering a sustainable product for use. Section two represented the latent variables of the STPB model [67][68][69][70][71][72][73][74][75][76][77][78][79][80], which are PI and PAS with (4) constructs each, CPV, SNs, AT, PBC, PENC, and PECC with (5) constructs each, to which all were taken from different studies shown in Table 1. The survey utilized 5 point-type Likert Scale (5 = strongly agree, 1 = strongly disagree) to evaluate the different constructs.…”
Section: Questionnairementioning
confidence: 99%
“…The demographics section included gender, age, status, area of residence, education level, employment, total monthly household income, and the frequency of considering a sustainable product for use. Section two represented the latent variables of the STPB model [67][68][69][70][71][72][73][74][75][76][77][78][79][80], which are PI and PAS with (4) constructs each, CPV, SNs, AT, PBC, PENC, and PECC with (5) constructs each, to which all were taken from different studies shown in Table 1. The survey utilized 5 point-type Likert Scale (5 = strongly agree, 1 = strongly disagree) to evaluate the different constructs.…”
Section: Questionnairementioning
confidence: 99%